PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Agustina, Liya; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to tests the influence of financial performance, firm size and company growth to the dividend policy. This research has been carried out by using quantitative approach and multiple linear analysis method. The data is the secondary data which has been obtained from manufacturing companies which are listed in Indonesia Stock Exchange in 2011-2013 periods. The data collection technique has been done by using documentation and literature study. The sampling has been done by using purposive sampling method. 15 companies which meet the criteria have been selected as samples so that the observation in this research are 45 observations. The results of this research indicate that liquidity and profitability variable has positive influence to the dividend policy. Leverage has positive influence to the dividend policy, it means that when the company liabilities is high, it does not mean that the dividend payment will be low. Firm size has positive influence to the dividend policy which means that when firm size is getting large, the turnover and the profit will be high as well. When the profit is high, it means that the ability of the company to pay dividend is higher than small firm. While company growth has negative influence to the dividend policy; it means that when the level of company growth is getting high, the fund that is needed to finance the needs in the future and the dividend that is needed to pay is getting small.Keywords: financial performance, firm size, company growth, dividend policy.